O regime constitucional da segurança cidadã - Fabretti, Humberto Barrionuevo (2013)
The thesis aims to analyze the failure of the Brazilian state to promote public safety in a satisfactory way and find the possible causes of this problem. For this presents and analyzes the main contemporary theories about the risk to check on what they can contribute to the study of public safety, especially as a tool for measuring and managing risks arising from crime. Through the analysis of doctrine and international documents presents the development of the concept of security from the eighteenth century to the twenty-first century, when there is the notion of citizen security. Develops a comparative study of the concepts public safety and citizen security. As regards the legal treatment given to public security in Brazil, analyzes the 1988 Federal Constitution, especially article 144, and faces the legal treatment and doctrinal conceptions of public order. Notes that the inability to provide public safety arises mainly the understanding of public safety as a means of maintaining public order, and the alleged existence of an individual right to security. Public safety directed to the maintenance of public order, by its authoritarian nature, justifies the practice of arbitrary acts. The claim of an individual's right to security is exclusionary because it can not be guaranteed so universal. Concluded that the public safety oriented not reach the protection of citizens and that this situation will only be possible by replacing the paradigm of public order by the paradigm of citizen security and the recognition of the right to security can not be enjoyed individually, but collective. The state should not base their actions in order to maintain public order on the grounds of preserving the individual right to security of some people, but to provide and maintain the rights of all citizens. The goal state should be the maintenance of the rights of citizens and not public order.